How Do Pre-School and/or School-Age Children Affect Parents' Likelihood of Migration and Off-Farm Work in Rural China's Minority Regions? - Sai Ding; Xiao-Yuan Dong; Margaret Maurer-Fazio (Institute for the Study of Labor (IZA), 2016)
In this paper we explore the intersectionality of religious and ethnic norms and gender relations across the domestic and public spheres of work in post-reform rural, minority-concentrated China. We focus on the role that children play in their parents' off-farm work decisions for three aggregated ethnic groups (majority Han, Muslim minorities, and non- Muslim minorities). We control for households' composition and economic characteristics and individuals' human capital and as well as local economic conditions. Children generally decrease women's willingness to work away from/outside the home and increase men's willingness to do so. When we focus specifically on the effects of pre-school children, our results suggest it is more socially acceptable for non-Muslim than Muslim women to work away from home. When we turn our attention to school-age children, the gender of the child becomes as important to the analysis as the gender of the parent. With regard to household composition, we find that in Muslim households the presence of extra adult men (of any age between 15 and 70) in the household reduces the likelihood that women engage in off-farm work. The presence in the household of a woman of grandmotherly age (between 46 and 70) supports Muslim minority women's ability to migrate for work. For non-Muslim households, grandfathers and grandmothers alike, facilitate the ability of parents (male and female) to migrate for work.
Keywords: J14; J15; J16; J26; D13; O53; 330; off-farm work; ethnicity; household composition; children; migration; China